Genome Analysis of Streptococcus pyogenes Associated with Pharyngitis and Skin Infections - Khazen, Georges (2016)
Streptococcus pyogenes is a very important human pathogen, commonly associated with skin or throat infections but can also cause life-threatening situations including sepsis, streptococcal toxic shock syndrome, and necrotizing fasciitis. Various studies involving typing and molecular characterization of S. pyogenes have been published to date; however next-generation sequencing (NGS) studies provide a comprehensive collection of an organism’s genetic variation. In this study, the genomes of nine S. pyogenes isolates associated with pharyngitis and skin infection were sequenced and studied for the presence of virulence genes, resistance elements, prophages, genomic recombination, and other genomic features. Additionally, a comparative phylogenetic analysis of the isolates with global clones highlighted their possible evolutionary lineage and their site of infection. The genomes were found to also house a multitude of features including gene regulation systems, virulence factors and antimicrobial resistance mechanisms.